Refractory/Relapsed Classic Hodgkin Lymphoma Mimicking Disseminated Tuberculosis - Mohamed Nazem Alibrahim; Hussein Hammam; Antonino Carbone; Noor Alsaleh; Annunziata Gloghini (Hemato)
Background/Objectives: Classic Hodgkin lymphoma (cHL) is a predominantly curable B-cell malignancy. However, primary refractory and relapsed (R/R) cHL remain therapeutic challenges, especially in regions with high tuberculosis (TB) prevalence, where clinical and radiologic features overlap and can obscure the correct diagnosis. This article, presenting a case of R/R cHL mimicking disseminated TB, reviews the evolving paradigm in R/R cHL management. Methods: A 30-year-old Middle Eastern male with advanced nodular sclerosis cHL initially achieved a complete remission (CR) with escalated BEACOPP chemotherapy. Shortly afterward, he developed respiratory symptoms and diffuse miliary pulmonary nodules, highly suggestive of disseminated TB. Despite extensive negative TB workup, including QuantiFERON-TB Gold testing, sputum acid-fast bacilli (AFB) staining, and PCR, his imaging raised concern for recurrent cHL. Due to the small size and diffuse distribution of nodules, biopsy was unfeasible, prompting empiric salvage therapy with DEHAP-Carbo, brentuximab vedotin (BV), and nivolumab. Results: The rapid and robust metabolic response on PET/CT supported lymphoma relapse rather than TB. Following four cycles of this combined regimen, he proceeded to autologous stem cell transplantation and achieved a second CR. Conclusions: This case highlights the diagnostic difficulties in differentiating cHL relapse from TB in endemic regions, emphasizes the critical role of PET/CT in guiding therapy when histopathological confirmation is impractical, and illustrates the impact of novel immunotherapies in improving outcomes. By underscoring the importance of early diagnostic suspicion and multimodal assessment, this article also reviews the evolving paradigm in R/R cHL management, where personalized approaches and targeted agents increasingly complement or replace traditional chemotherapy regimens.